2011
DOI: 10.4238/vol10-2gmr1088
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of the organ-specific and light-inducible promoter of the gene encoding rubisco activase in potato (Solanum tuberosum)

et al.

Abstract: ABSTRACT. Constitutive promoters have been widely used in crop biotechnology applications. Tissue-specific or inducible promoters, however, have advantages in some cases. We isolated the 731-bp 5' flanking sequence of a potato (Solanum tuberosum) gene, encoding ribulose-1,5-bisphosphate carboxylase/oxygenase (rubisco) activase (RCA), which was isolated by genome walking. By using GUS as a reporter and with Northern blot analysis, the 702-bp fragment (referred to as StRCAp), ranging from nt -731 to -30 relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 45 publications
0
17
0
1
Order By: Relevance
“…To identify whether sequence polymorphisms in the promoter region of GmRCAβ were related to the observed expression level, a 2300-bp region of the promoter, which was shown to be sufficient for the proper regulation of expression in plant (Orozco and Ogren, 1993; Liu et al , 1996; Qu et al , 2011; Yang et al , 2012), was cloned and sequenced, including the promoter and the 5′-UTR region, in a natural population including 219 landraces of different geographic origins (Supplementary Figs S4 and S5). Multiple sequence alignment revealed 16 polymorphic sites and five types of sequences (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify whether sequence polymorphisms in the promoter region of GmRCAβ were related to the observed expression level, a 2300-bp region of the promoter, which was shown to be sufficient for the proper regulation of expression in plant (Orozco and Ogren, 1993; Liu et al , 1996; Qu et al , 2011; Yang et al , 2012), was cloned and sequenced, including the promoter and the 5′-UTR region, in a natural population including 219 landraces of different geographic origins (Supplementary Figs S4 and S5). Multiple sequence alignment revealed 16 polymorphic sites and five types of sequences (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, seven SNPs were identified as significantly associated with the expression of GmRCAβ (Table 5). Interestingly, three SNPs were located in regulatory elements such as the AT1 motif and the TATA box, which are important for the light regulation of gene expression, and data gathered in several species indicate that the expression of RCA is highly regulated by light (Qu et al , 2011). These SNPs in regulatory regions may impact the phenotype by altering the activity of the promoter and changing the expression levels of the RCA genes (Kumar et al , 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4) GATA motifs (WGATAR); these are implicated to act in the light-dependent and nitrate-dependent control of transcription in plants (Reyes et al, 2004). 5) Motifs with a known relationship to light including H box (CCTACC), REalpha element (AACCAA), and CCAAT-box (Song et al, 2000;Outchkourov et al, 2003;Qu et al, 2011). The cis-acting elements identified in rbcSP strongly suggested that heterologous genes driven by rbcSP could be induced in a lightspecific manner.…”
Section: Sequence Analysis Of the Soybean Rbcs Promotermentioning
confidence: 99%
“…The rbcS promoter has been cloned, sequenced, and studied in various plants, including pea (Pisum sativum; Nagy et al, 1985), cotton (Gossypium spp; Song et al, 2000), Chrysanthemum (Outchkourov et al, 2003), coffee (Coffea arabica; Marraccini et al, 2003), and potato (Solanum tuberosum L.; Qu et al, 2011). In soybean, the rbcS gene family comprises 6-10 members (Dean et al, 1989).…”
Section: Introductionmentioning
confidence: 99%